In search for optimal induction chemotherapy for advanced nasopharyngeal cancer: Standard dosing of Docetaxel, Platinum, and 5-Fluorouracil (TPF) followed by chemoradiation. - Michelle Jun; Harlan Pinto; Quynh-Thu Le; Andrew Quon; Wendy Hara; Jessie Coty; Alex McMillan; Rong Lu; Elzbieta Winters; Ruth Lira; A Dimitrios Colevas (PLoS ONE)
Objectives A phase II = design is used to evaluate the efficacy and feasibility of full dose docetaxel, platinum, and 5-fluorouracil (TPF) in a sequential chemoradiation treatment locally advanced (LA) or oligometastatic (OM) NPC patients. Materials and methods Twenty patients with LANPC (M0 cohort) and six patients with OMNPC (M1 cohort) received induction standard dose T (75 mg/m2) P (75 mg/m2) F (750 mg/m2 IVCI x 5days) x 3 followed by weekly cisplatin (40 mg/m2) or carboplatin (AUC 1.5) x 6 concurrent with radiation therapy of 70 Gy over 6.5-7 weeks. The first five patients received bevacizumab as part of an exploratory objective of hypoxia modification using correlative fluoromisonidasole (18F-MISO) PET CT scanning. Results The 18F-MISO imaging failed to reveal adequate levels of baseline hypoxia necessary to evaluate for changes with chemotherapy and bevacizumab. Ninety percent of M0 patients and 83% of M1 patients received the full-intended TPF and radiation dose. Eighty-five percent of M0 patients and all M1 patients received at least 60% of the full-intended concurrent platinum dose. The 2-year progression free survival (PFS) rate for the M0 cohort was 90% (95% CI: 77.8%- 100%), and was sustained at 5 years. The 2-year PFS rate for the M1 cohort was 66.7% (95% CI: 37.9%- 100%). The 2-year overall survival (OS) rates for the M0 and M1 cohorts were 100% and 83.3% (95% CI: 58.3%- 100%), respectively. At five years, OS was 94.4% for the M0 cohort. Conclusion Administration of standard-dose TPF as induction chemotherapy in this NPC patient population is both feasible and effective when coupled with definitive concurrent chemoradiation. Clinicaltrials.gov identifier NCT00896181.